The many faces of evil theological systems and the problem of evil - Feinberg, John S. 1946- (Grand Rapids, MI Zondervan, 1994)
Includes bibliographical references and index
First edition published 1979.
Keywords: Theodicy; Good and evil; Providence and government of God; Free will and determinism; Suffering -- religious aspects -- Christianity